Role of Cultural Intelligence, Social Adjustment and Spiritual Intelligence on Mental Health - Slathia, Sumedha (My University, 2019)
The present study examined the effect of Cultural Intelligence, Spiritual Intelligence, and Social Adjustment on Mental Health of the individuals who have worked and lived away from their local area and had interactions with people from various cultural backgrounds. This study was conducted on 100 participants, which include both male and female participants. The individuals from 30 to 50 years of age were included. The questionnaires used were: Four Factor Cultural Intelligence Scale (CQS), (SSRI- 24) The Spiritual Intelligence self – report Inventory, Social Adjustment Inventory, The Mental Health Continuum – (MHC – SF) Keyes, 2005. Results revealed that Cultural Intelligence, Spiritual Intelligence and Social Adjustment have significant relationship with Mental Health (wellbeing).
Keywords: CULTURAL INTELLIGENCE; SOCIAL ADJUSTMENT; SPIRITUAL INTELLIGENCE; MENTAL HEALTH